Three-dimensional sensing of the magnetic-field vector by a compact planar-type Hall device - Junichi Shiogai (Nature Portfolio, 2021)
Three-dimensional magnetometers are key for detecting the motion of objects in automated electronics, but typically require multiple sensors on orthogonal planes. Here, a compact planar-type 3D magnetometer with low power consumption is realized using a topological ferromagnetic Fe-Sn heterostructure.